An Overview Of Needs Analysis In The Field Of English For Specific Purposes And Some Case Studies In The Occupational Sector - Asma Merine; Mohamed Yamine BOULENOUAR (Al-Lisaniyyat)
This paper aims at providing a theoretical overview of the significance of ‘Needs Analysis’ (henceforth, (NA)) as a corner stone in designing ESP courses. First, it summarises the most frequently used definitions of ESPand its main sub-divisions. Then, it reviews the history and development of NA, the notion of needs analysis in ESP setting and some important components of needs analysis process. The most influential models in NA are presented briefly, beginning with Munby’s model (1978) which paved the way for course designers to design effective courses in different specific areas needed by learners and workers at the workplace. The purpose of this paper is two-fold: 1) to present some previous case studies related to different occupations in different countries that have focused on the needs of the situational settings; 2) to explore the most effective methods to conduct needs analysis in occupational settings.